Effect of hydration status on high-intensity rowing performance and immune function - Penkman, M. A.; Field, C. J.; Sellar, J. M.; Harber, V. J.; Bell, G. J. (International Journal of Sports Physiology and Performance, 2008)
Purpose: This study determined the effect of dehydration and rehydration (DR) on performance, immune cell response, and tympanic temperature after high-intensity rowing exercise. Methods: Seven oarswomen completed two simulated 2000-m rowing race trials separated by 72 h in a random, cross-over design. One trial was completed in a euhydrated (E) condition and the other using a DR protocol. Results: The DR condition resulted in a 3.33 ± 0.14% reduction in body mass (P < .05) over a 24-h period followed by a 2-h rehydration period immediately before the simulated rowing race. There was a greater change in tympanic temperature observed in the DR trial (P < .05). There were increases in the blood concentration of leukocytes, lymphocytes, lymphocyte subsets (CD3+, CD3+/4+, CD3+/8+, CD3-/16+, CD4+/25+; P < .05) and decreases in lymphocyte proliferation and neutrophil oxidative burst activity immediately following the simulated race (P < .05) in both trials. Blood leukocyte and neutrophil concentrations were greater after exercise in the DR trial (P < .05). Whereas most immune measures returned to resting values after 60 min of recovery in both trials, lymphocyte proliferation and the concentrations of CD3+/4+ and CD4+/25+ cells were significantly lower than before exercise. Blood leukocyte and neutrophil concentrations were significantly higher before and after exercise in the E trial. Conclusion: The effects of dehydration/rehydration did not negatively influence simulated 2000-m rowing race performance in lightweight oarswomen but did produce a higher tympanic temperature and had a differential effect on blood leukocyte, neutrophil, and natural killer (CD3-/16+) cell concentrations after exercise compared with the euhydrated state.